Subsequent chemotherapy with paclitaxel plus cetuximab-based chemotherapy following immune checkpoint inhibitor in recurrent or metastatic squamous cell carcinoma of the head and neck - Tanaka, Hideki; Enokida, Tomohiro; Okano, Susumu; Fujisawa, Takao; Tanaka, Nobukazu; Takeshita, Naohiro; Onaga, Ryutaro; Hoshi, Yuta; Wada, Akihisa; Sato, Masanobu; Ueda, Yuri; Tahara, Makoto (Frontiers in Oncology, 2023)
Background Immune checkpoint inhibitors (ICIs) are essential in treating recurrent/metastatic squamous cell carcinoma of the head and neck (R/M SCCHN). However, the overall response rate (ORR) is limited to 10-20%, and subsequent chemotherapy is critical to maximizing the subjects’ prognosis. Methods We retrospectively reviewed 59 patients with R/M SCCHN treated with paclitaxel+cetuximab (PE)-based chemotherapy (PCE, paclitaxel+carboplatin+cetuximab; or PTX+Cmab, paclitaxel+cetuximab) following disease progression after either pembrolizumab or nivolumab monotherapy. Results Of 59 patients, 15 were treated with pembrolizumab, with an ORR of 13.3%, and the remaining 44 with nivolumab, with an ORR of 11.4%. All patients in the pembrolizumab cohort had platinum-sensitive disease. Following ICI treatment, 19 patients were treated with PCE and the remaining 40 with PTX+Cmab. PE-based chemotherapy induced favorable and prompt tumor shrinkage even in cases where ICI was not effective, with a median change in the summed dimensions of target lesions of -43.4%, resulting in an ORR of 62.7%. Median time to response was 1.8 months. The patients in the pembrolizumab cohort appeared to have a numerically higher response rate than those receiving nivolumab (80.0% vs. 56.8%). For the 59 patients, progression-free survival and overall survival, calculated from the initiation of PE-based chemotherapy, were 4.6 months and 17.1 months, respectively. Grade ≥3 adverse events occurred in 40.7%, and no treatment-related death was observed. Conclusion PE-based chemotherapy following ICI is encouraging for its robust antitumor efficacy in R/M SCCHN.